2011
DOI: 10.1002/jcp.22431
|View full text |Cite
|
Sign up to set email alerts
|

KIT receptor activation by autocrine and paracrine stem cell factor stimulates growth of merkel cell carcinoma in vitro

Abstract: The co-expression of KIT receptor and its ligand stem cell factor (SCF) has been reported in biopsy specimens of Merkel cell carcinoma (MCC). However, the functional role of SCF/KIT in the pathogenesis of this aggressive tumor has not been elucidated. The present study reports expression and effects of SCF and KIT in the Merkel cell carcinoma cell line MCC-1 in vitro. SCF and KIT were endogenously co-expressed in MCC-1 cells. Exogenous soluble SCF modulated KIT receptor mRNA and protein expression, stimulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 53 publications
1
21
0
1
Order By: Relevance
“…Thus, KIT in colon cancer appears to have a functionally-important growth-promoting role through KITLG, either in an autocrine and/or paracrine manner as shown by our single cell gene expression analysis, and in agreement with previous in vitro studies in colon and other cancers 18,31,32 . This is surprising because KIT signaling currently has no known functional role in normal colonocytes 33 .…”
Section: Discussionsupporting
confidence: 92%
“…Thus, KIT in colon cancer appears to have a functionally-important growth-promoting role through KITLG, either in an autocrine and/or paracrine manner as shown by our single cell gene expression analysis, and in agreement with previous in vitro studies in colon and other cancers 18,31,32 . This is surprising because KIT signaling currently has no known functional role in normal colonocytes 33 .…”
Section: Discussionsupporting
confidence: 92%
“…Although recent studies indicated that systemic infusion of BMSC-conditioned medium improved survival in a small-animal (rat) model of FHF,16 30 certain components may be potentially harmful 31 32. Searching for key therapeutic molecules that may be useful for developing a balanced cocktail, instead of whole cells, is emerging as an exciting concept in regenerative medicine.…”
Section: Discussionmentioning
confidence: 99%
“…SCF is a multifunctional factor. The membrane-bound form of SCF promotes the cell proliferation and is important in tumor growth and angiogenesis (Krasagakis et al 2011). Hypoxia can increase the expression of SCF in breast cancer cells and astrocytes (Xu et al 2007;Han et al 2008).…”
Section: Discussionmentioning
confidence: 99%